2004
DOI: 10.1002/rcm.1413
|View full text |Cite
|
Sign up to set email alerts
|

Determination of brassinosteroids in the sub‐femtomolar range using dansyl‐3‐aminophenylboronate derivatization and electrospray mass spectrometry

Abstract: A selective and sensitive electrospray ionization (ESI) mass spectrometry based method for detection of brassinosteroids (BS) in plant samples was developed. The limit of detection (LOD) was dramatically reduced over existing analytical methods using a microbore (1.00 mm) C18 column and chemical derivatization of free BS to dansyl-3-aminophenylboronates. The LOD in the selected-ion monitoring (SIM) mode for derivatized BS was 125 attomole (signal-to-noise ratio 3). The practical utility of the method is docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 14 publications
(14 reference statements)
0
31
0
Order By: Relevance
“…Triply deuterated brassinosteroids, [26-2 H 3 ]3-epicastasterone, and [26-2 H 3 ]3-epibrassinolide [31] (0.4 µg in 10 µl of 75% EtOH each), were added as internal standards. Several solvent partitioning and chromatographic steps resulted in brassinosteroid-containing fractions, which after derivatization with an excess of dansyl-3-aminophenylboronic acid were analyzed by liquid chromatography (HPLC) with electrospray ionization (ESI) and using an established selected ion-monitoring mass-spectrometric (SIM-MS) detection (HPLC-ESI-SIM-MS) method [10,32]. Identification of brassinosteroids based on the relative retention time of 22,23-dansyl-3-aminophenylboronates (Table 1).…”
Section: Brassinosteroids In Arabidopsis Thaliana and Secale Cerealementioning
confidence: 99%
See 2 more Smart Citations
“…Triply deuterated brassinosteroids, [26-2 H 3 ]3-epicastasterone, and [26-2 H 3 ]3-epibrassinolide [31] (0.4 µg in 10 µl of 75% EtOH each), were added as internal standards. Several solvent partitioning and chromatographic steps resulted in brassinosteroid-containing fractions, which after derivatization with an excess of dansyl-3-aminophenylboronic acid were analyzed by liquid chromatography (HPLC) with electrospray ionization (ESI) and using an established selected ion-monitoring mass-spectrometric (SIM-MS) detection (HPLC-ESI-SIM-MS) method [10,32]. Identification of brassinosteroids based on the relative retention time of 22,23-dansyl-3-aminophenylboronates (Table 1).…”
Section: Brassinosteroids In Arabidopsis Thaliana and Secale Cerealementioning
confidence: 99%
“…After a two-day incubation, the plant material was extracted according to the procedure used to detect endogenous brassinosteroids. Brassinosteroid-containing fractions were converted to their dansyl-3-aminophenylboronates and analyzed by HPLC-ESI-SIM-MS [10,32].…”
Section: Brassinosteroids In Arabidopsis Thaliana and Secale Cerealementioning
confidence: 99%
See 1 more Smart Citation
“…Derivatization protocols References Diazomethane Sample was methylated using a stream of diazomethane gas [30] Sample was dissolved in 10% (v/v) methanol in diethylether and was methylated by reaction with diazomethane for 10 min at 0°C [7] Incubate at room temperature in methanol solution [81,90] creasing the volatility of plant hormones, so that the derived plant hormones are more suitable for GC/MS analysis. Although LC/MS can analyze plant hormones directly, derivatization is employed to improve ionization efficiency of the derived hormones, which can improve sensitivity by 10-to 1000-fold compared with underived hormones, and so has received increasing attention for the analysis of plant hormones [86][87][88].…”
Section: Chromatography and Chromatography/mass Spectrometrymentioning
confidence: 99%
“…Yamashita et al reported a sensitive and specific assay method for estrogen o-quinones using LC/ESI-MS/MS combined with the o-phenylenediamine-derivatization. 7) Brassinosteroids (vicinal diol-containing plant hormones) were also analyzed by a derivatization followed by LC/ESI-MS. 8) However, to the best of our knowledge, a practical derivatization procedure specific for the bioanalysis of steroids having a vicinal diol has not been reported.…”
mentioning
confidence: 99%